Pedestrian Fall Safety Assessments Improved Understanding on Slip Resistance Measurements and Investigations - Kim, In-Ju.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book examines pedestrian shoe-floor slip resistance from an engineering standpoint in order to better understand friction and wear behavior. This analysis includes an extensive investigation into the surface properties of shoes and flow, and the measurement of dynamic friction and other mechanical and physical aspects of shoe-floor tribology. Lastly, the book proposes a measurement concept for the identification and classification of operational floor surfaces under a range of different conditions. Novel techniques and methods are proposed that can improve the reliability of slip resistance assessments. The current state of knowledge is critically examined and discussed from a tribological perspective, including aspects like friction, wear, lubrication and the mechanical behavior of shoes, floors and their wider environment. Further, the book reports on extensive experimental investigations into the topographical characteristics of shoe and floor surfaces and how they affect slip resistance. Slips resulting in pedestrian falls are a major cause of injuries and deaths for all age groups. This important book provides essential insights for researchers, practicing engineers and public safety officials wishing to learn about how the risk of pedestrian slips can be assessed and understood.
Chapter 1. Introduction -- Chapter 2. Pedestrian Falls and Slip Resistance Measurements -- Chapter 3. Pedestrian Slip Resistance Measurements: Verities and Challenges -- Chapter 4. Tribological Approaches for Fall Safety Measurements and Assessments -- Chapter 5. Friction and Wear Behaviours of the Shoe-Floor Sliding Friction System -- Chapter 6. Surface Measurement and Analysis for Shoes and Floors -- Chapter 7. Practical Design Search for Optimal Floor Surface Finishes -- Chapter 8. Future Works -- Index.
Keywords: Security systems; Coatings; Tribology; Corrosion and anti-corrosives.; Buildings -- Design and construction; Surfaces (Technology).; Thin films; Security Science and Technology; Coatings; Tribology; Corrosion; Building Construction and Design; Surfaces, Interfaces and Thin Film